2016
DOI: 10.1101/gad.277137.115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insights into the mechanisms of Fgf signaling

Abstract: The fibroblast growth factor (Fgf) family of ligands and receptor tyrosine kinases is required throughout embryonic and postnatal development and also regulates multiple homeostatic functions in the adult. Aberrant Fgf signaling causes many congenital disorders and underlies multiple forms of cancer. Understanding the mechanisms that govern Fgf signaling is therefore important to appreciate many aspects of Fgf biology and disease. Here we review the mechanisms of Fgf signaling by focusing on genetic strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
206
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(208 citation statements)
references
References 254 publications
(348 reference statements)
1
206
0
1
Order By: Relevance
“…Conversely, it is possible that HSPG co-receptors may facilitate Fgf4 engagement of receptors expressed in PrE, as previous studies have demonstrated that HSPGs are essential for promoting paracrine signaling (Cai et al, 2014; Shimokawa et al, 2011). Second, as Fgf signaling is known to engage a number of signaling pathways in addition to Erk (Brewer et al, 2016), it is also possible that the signaling pathways engaged by Fgfr1 or Fgfr2 are different, or vary between the Epi and the PrE precursor cells. It is also possible that the duration of signaling varies in different cell types, promoting cell differentiation (Brewer et al, 2016; Marshall, 1995; Vasudevan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, it is possible that HSPG co-receptors may facilitate Fgf4 engagement of receptors expressed in PrE, as previous studies have demonstrated that HSPGs are essential for promoting paracrine signaling (Cai et al, 2014; Shimokawa et al, 2011). Second, as Fgf signaling is known to engage a number of signaling pathways in addition to Erk (Brewer et al, 2016), it is also possible that the signaling pathways engaged by Fgfr1 or Fgfr2 are different, or vary between the Epi and the PrE precursor cells. It is also possible that the duration of signaling varies in different cell types, promoting cell differentiation (Brewer et al, 2016; Marshall, 1995; Vasudevan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Second, as Fgf signaling is known to engage a number of signaling pathways in addition to Erk (Brewer et al, 2016), it is also possible that the signaling pathways engaged by Fgfr1 or Fgfr2 are different, or vary between the Epi and the PrE precursor cells. It is also possible that the duration of signaling varies in different cell types, promoting cell differentiation (Brewer et al, 2016; Marshall, 1995; Vasudevan et al, 2015). Although Erk1/2 is a prominent pathway engaged by Fgf signaling (Brewer et al, 2016; Brewer et al, 2015; Lanner and Rossant, 2010), how Fgf signaling regulates PrE specification genes through Erk and other pathways remains incompletely understood, and assessing signaling mechanisms in PrE formation and in the exit from pluripotency will require further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGFR signaling activates at least four downstream intracellular signaling pathways including, MAPK, PI3K/AKT, PLCγ, and STATs (reviewed in Ornitz and Itoh, 2015; Brewer et al, 2016). In the growth plate, FGFR3 activates STAT1 and the ERK1/2 and p38 branches of the MAPK pathway (Figure 2) (Su et al, 1997; Chen et al, 1999; Li et al, 1999; Chen et al, 2001; Legeai-Mallet et al, 2004; Raucci et al, 2004; de Frutos et al, 2007; Parafioriti et al, 2009).…”
Section: Fgfr3 Signaling In the Growth Platementioning
confidence: 99%
“…Abnormal FGF signaling is linked to many congenital disorders as well as cancers (Beenken and Mohammadi, 2009; Brewer et al, 2016; Turner and Grose, 2010). Understanding the fundamental basis of FGF signaling is the key to uncover mechanisms of development and diseases.…”
Section: Introductionmentioning
confidence: 99%